A Systematic Review of Race/Ethnicity and Parental Treatment Decision-making - Harris, Vandra C. (Clin Pediatr (Phila), 2018)
Patient race/ethnicity impacts healthcare utilization, provider trust, and treatment choice. It is uncertain how these influences affect pediatric care. We performed a systematic review (PubMed, Scopus, Web of Science, PsycINFO, Cochrane and Embase) for articles examining race/ethnicity and parental treatment decision-making, adhering to PRISMA methodology. 9200 studies were identified, and 17 met inclusion criteria. Studies focused on treatment decisions concerning end-of-life care, HPV vaccination, urological surgery, medication regimens, and dental care. Findings were not uniform between studies, however pooled results showed 1) racial/ethnic minorities tended to prefer more aggressive end-of-life care; 2) Familial tradition of neonatal circumcision influenced the decision to circumcise and 3) Non-Hispanic Whites were less likely to pursue HPV vaccination but more likely to complete the vaccine series if initiated. The paucity of studies precluded overarching findings regarding the influence of race/ethnicity on parental treatment decisions. Further investigation may improve family-centered communication, parent engagement, and shared decision-making.